(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article undertakes a comprehensive exploration of the integration of artificial intelligence (AI) in the financial sectors of developing, underdeveloped nations. Analyzing the unique challenges and hindrances faced in implementing AI technologies, the study presents a multifaceted view of the landscape and prospects for future growth. Drawing lessons from developed countries and spotlighting precise recommendations, it paves the way for enhancing AI adoption in these diverse contexts. The findings reveal significant barriers that must be overcome but also highlight potential pathways for substantial advancements through correct strategic planning. The case of Uzbekistan, in particular, is examined to illustrate both the complexities and the opportunities inherent in this transformative journey towards financial innovation.